Plant-aphid interactions with a focus on legumes - Kamphuis, L.; Zulak, Katherine; Gao, L.; Anderson, J.; Singh, K. (2013)
Sap-sucking insects such as aphids cause substantial yield losses in agriculture by draining plant nutrients as well as vectoring viruses. The main method of control in agriculture is through the application of insecticides. However, aphids rapidly evolve mechanisms to detoxify these, so there is a need to develop durable plant resistance to these damaging insect pests. The focus of this review is on aphid interactions with legumes, but work on aphid interactions with other plants, particularly Arabidopsis and tomato is also discussed. This review covers advances on the plant side of the interaction, including the identification of major resistance genes and quantitative trait loci conferring aphid resistance in legumes, basal and resistance gene mediated defence signalling following aphid infestation and the role of specialised metabolites. On the aphid side of the interaction, this review covers what is known about aphid effector proteins and aphid detoxification enzymes. Recent advances in these areas have provided insight into mechanisms underlying resistance to aphids and the strategies used by aphids for successful infestations and have significant impacts for the delivery of durable resistance to aphids in legume crops.